Punkt Informacyjno-Koordynacyjny dla Osób Niepełnosprawnością (PIKON) jako wsparcie informacyjne na rzecz poprawy jakości życia osób z niepełnosprawnościami i ich rodzin - Serafin, Teresa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
This article presents, undertaken by social organizations and the office of the Capital City of Warsaw, initiatives aimed at developing a model of cooperation between institutions performing tasks in the field of various areas of social policy. These initiatives concern, inter alia, continuing the activities of the education system in the field of equalizing the chances of students with disabilities by institutions performing tasks in the field of various areas of social policy, including those supporting professional and personal functioning of adults. One of the directions of this objective is the creation of an information and coordination point to support adults with disabilities in solving their problems, eg by providing information on possible participation in social rehabilitation and / or employment in an open, supported or protected labor market.